A Rapid Review on Advanced Software-in-the-Loop Methods for Automotive Software Verification - Pestana, Larissa; Miranda, Breno (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST), 2024)
The V-cycle has been the primary software development methodology in the automotive sector. However, with the increasing complexity of software, both from an architectural and technological perspective, software verification has become inefficient compared to system verification. This inefficiency results in rework and increased costs due to late error detection. Software deemed functional during verification may prove ineffective when tested in the simulated vehicle environment, as development requirements are ever-expanding, and test simulation environments have not kept pace with this evolution. The simulation environments used in automotive development are based on a guided simulation approach, encompassing Model-in-the-Loop (MiL), Software-in-the-Loop (SiL), Processor-in-the-Loop (PiL), and Hardware-in-the-Loop (HiL) testing. These tests are conducted between system and software verification and must be used in conjunction to achieve comprehensive validation. To address inefficiencies in software verification, techniques such as MiL, SiL, and PiL are excellent techniques. SiL, in particular, plays an essencial role in simulating code before its integration into the system. This rapid review will discuss techniques that make simulations more representative of the real vehicle system, considering the electromechanical structure of sensors and actuators outlined in the software requirements, as well as the network of ECUs, which follows a distributed communication model.